Septic arthritis of the hip in adults with sickle cell anemia - Poignard, Alexandre (PAGEPress Publications, 2011)
Although the presence of osteonecrotic bone is known to make joints more prone to infection, acute septic joint in hip osteonecrosis has not frequently been reported in adults with sickle cell disease. The clinical features at the time of admission, imaging findings suggesting the diagnosis, modes of treatment and sequelae of septic arthritis of twenty-four hip joints with osteonecrosis in patients with sickle cell disease were studied retrospectively over a 25-years period. This study evaluated also the complications, the efficiency and the risk of total hip arthroplasty in these patients. Most patients were in the third decade of life. Staphylococcus and Gram negative infection predominated. Treatment was first conservative but most of the patients needed surgery to treat infection and sequelae related to infection. A total hip arthroplasty was performed later in twenty joints. No deaths were observed, but complications occurred. Twenty of the patients in our study underwent delayed total hip arthroplasties following repeated aspirations of the joint and intravenous antibiotics. With an experienced surgical and medical team and multidisciplinary management of these patients undergoing total hip arthroplasty after hip infection, our rate of complications was acceptable.